Assessing The Readiness To Implement Quality Management Standards 1 - Nasran, Muchammad Asy’ari Mashbur (Eduvest - Journal of Universal Studies, 2025)
This study examines the readiness of MUN Public Accounting Firm (KAP MUN) to implement Standard on Quality Management 1 (SQM 1). The research employs single case study with a single unit of analysis. Interview data were evaluated using content analysis and thematic analysis with the aid of NVivo 15 software. The research result shows that KAP MUN has not fully implemented IFAC small firm implementation installment indicators steps and faces challenges across all three key determinants of implementation capability, which negatively affects its readiness to adopt SQM 1. Sole proprietorship accounting firms like KAP MUN are inadequately prepared to implement SQM 1. Regulatory bodies and professional organizations should provide enhanced support for sole proprietorship accounting firms. The novelty of this research is that it discusses SQM 1 and applies the IFAC small firm implementation installment indicators alongside three key determinants of implementation capability to assess readiness for SQM 1 implementation.